The Influence of Compensation and E-Recruitment on Job Application Interest with Company Reputation as a Mediation Variable Among Final-Year Students - Nandita Annisa Fitri Yani; Andriyastuti Suratman (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
The growth of the population has led to an increase in the workforce and the supply of labor in the labor market, driving significant development in Indonesia’s labor market, including more job opportunities and a decrease in the unemployment rate. Companies, as key drivers of the labor market, are essential in providing job opportunities and stimulating economic growth. To stay competitive, companies must not only focus on profitability but also attract and retain skilled employees. This requires optimizing productivity and ensuring that workers improve both soft and hard skills to meet company needs. Furthermore, companies face intense competition in recruiting the best talent, which becomes a key factor in achieving a competitive advantage.